Ética y humnitarismo. Dimensiones morales de la ayuda humanitaria desde la perspectiva de Thomas Pogge - Belli, Laura F.; Quadrelli, Silvia (Nómadas. Critical Journal of Social and Juridical Science, 2011)
For the last 20 years the amount of deaths because of hunger and diseases that could be avoided affects approximately 250 million people. Thomas Pogge affirms that the rich countries have the responsibility to help the other countries that are sunk in severe poverty. This responsibility –that could also be understood as moral duty– comes from the damage, often avoidable, that the present global institutional order has perpetrated upon poor States. Global poverty, according to this author, is a clear violation of the human rights, as well as a crime towards humanity.